Characterizing health services interventions for evidence syntheses by using the theme, intensity, provider/platform (TIP) framework. Issue 4 (18th December 2022) - Dhippayom, Teerapon; Saldanha, Ian J.; Chaiyakunapruk, Nathorn; Devine, Beth
Abstract: Health services interventions comprise a range of elements and procedures that contribute to their effects. However, there is currently limited guidance to systematically classify different features of health services interventions. We propose an approach to aid in classifying health services interventions using three potential elements: theme, intensity, and provider/platform (TIP). We designed the TIP framework to be analogous to three elements of a medication intervention that contribute to its pharmaceutical effects: 1) active ingredient, 2) dose, and 3) dosage form or route of administration. Health services interventions encompass similar elements: 1) "theme", which corresponds to the active ingredient and specifies the main element of the intervention; 2) "intensity", which corresponds to the dose regimen; and 3) "provider" or "platform", which corresponds to the dosage form or route of administration and indicates how the main element is delivered. Each health services intervention can be classified into a set of unique TIP features, which can then be compared with others using either a qualitative or qualitative approach. The TIP framework is not suitable for multicomponent health services interventions, in which a singular main theme or active component cannot be identified. The TIP framework enables researchers to systematically characterize health services interventions according to their unique features that contribute to its effects. It also helps to generate evidence to determine not only what service is more effective, but also how to best deliver such service.